1999
DOI: 10.1063/1.370197
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort-pulse laser machining of dielectric materials

Abstract: There is a strong deviation from the usual 1/2 scaling of laser damage fluence for pulses below 10 ps in dielectric materials. This behavior is a result of the transition from a thermally dominated damage mechanism to one dominated by plasma formation on a time scale too short for significant energy transfer to the lattice. This new mechanism of damage ͑material removal͒ is accompanied by a qualitative change in the morphology of the interaction site and essentially no collateral damage. High precision machini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
222
0
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(241 citation statements)
references
References 19 publications
12
222
0
7
Order By: Relevance
“…The interaction of high-intensity and ultra-short electromagnetic fields with condensed matter is an important subject from both fundamental and technological points of view [1][2][3][4]. To investigate dynamics of electrons and phonons in real time, the pump-probe experimental technique has been extensively employed.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of high-intensity and ultra-short electromagnetic fields with condensed matter is an important subject from both fundamental and technological points of view [1][2][3][4]. To investigate dynamics of electrons and phonons in real time, the pump-probe experimental technique has been extensively employed.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments showed that the ablation rate in dentin is approximately 1 ~m/pulse which corresponds to removal of 1 mm/sec using a 1 kHz repetition rate system. Scanning electron microscopy (SEM) studies verified lack of collateral damage at the ablation craters [5,6,7,8].…”
Section: Yearmentioning
confidence: 91%
“…A computer-controlled feedback system utilized the high intensity luminescence of calcium at 616 nm and it was used in selective ablation of the bone tissues successfully [10]. Ablation thresholds were measured for hard dental tissues (dentin) and water and it was found that the threshold increases at longer pulse widths [6,11]. It was found that the threshold increased as the square root of pulse width for pulses longer than several picoseconds.…”
Section: Yearmentioning
confidence: 99%
“…The breakdown takes place when the plasma originated by the avalanche electrons reaches a critical density and transfers energy to lattice ions, which expand away from the surface after the pulse has finished. In metals, the seed electrons are always present (conduction band free electrons), and in dielectrics and semiconductors they are excited from the valence to the conduction band by the pulse leading edge, either by multiphotonic ionization (Kautek et al, 1996;Perry et al, 1999) or by tunneling induced by the laser field (Keldysh, 1965;Lenzner et al, 1998). Although the seed electrons have dissimilar origins in different classes of materials, a metallization occurs in dielectrics and semiconductors after they are produced, and the avalanche evolves deterministically in time (Bass & Fradin, 1973;Du et al, 1994;Joglekar et al, 2003) in the same way in all solids, that behave like metals (Gamaly et al, 2002;Nolte et al, 1997).…”
Section: Ionization By Ultrashort Pulsesmentioning
confidence: 99%